High incidence of vanadium and copper in the titanomagnetite and ilmenite samples off Ratnagiri, Maharashtra, India (Indian Journal of Geo-Marine Sciences (IJMS), 2025)
Samples of ilmenite and titanomagnetite collected off Ratnagiri and nearby bays exhibit elevated concentrations of vanadium and copper. In ilmenite, vanadium values range from 1429 to 1816 ppm, with an average of 1592 ppm. Titanomagnetite samples show vanadium concentrations ranging from 3392 to 4442 ppm (average = 4026 ppm). Copper values for ilmenite samples range from 345 to 1166 ppm, averaging 628 ppm, while titanomagnetite samples display copper values from 743 to 1030 ppm, averaging 943 ppm. The ternary diagram of TiO2, FeO and Fe2O3 indicates that all the magnetite samples with a higher concentration of vanadium and copper fall in the titanomagnetite field. From the ternary diagram, it is interpreted that the higher concentration of vanadium in the samples is contributed by titanomagnetite in the survey area, which is reported from the Deccan basalt present in the hinterland. The strong positive correlation between Cu and V further supports the provenance of titanomagnetite from the Deccan basalt.